The language of peace, communicating to create harmony - Simon, Mumbua (In Factis Pax: Journal of Peace Education and Social Justice, 2016)
The language of peace, communicating to create harmony, edited by Rebecca L. Oxford. A volume in the series: Peace Education, editors Laura Finley & Robin Cooper, Information Age Publishing, 2013, 355pp.US $39.09 (soft cover), US $73.09 (hardcover), ISBN 1623960940. Editors note: This review is one in a series co-published by the Global Campaign for Peace Education and In Factis Pax: Journal of Peace Education and Social Justice toward promoting peace education scholarship. These reviews are of Information AgePublishing’s Peace Education series. Established in 2006 by Founding Editors Ian Harris and Edward Brantmeier, IAP’s peace education series offers diverse perspectives on peace education theory, research, curriculum development and practice. It is the only series focused on peace education offered by any major publisher. Click here to learn more about this important series.